2003
DOI: 10.1002/pssc.200303304
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of surface contact potential of AlGaN/GaN heterostructure and n‐GaN by Kelvin probe force microscopy

Abstract: The contact potential images of the AlGaN/GaN heterostructure and n-GaN before and after thermal treatment have been successfully obtained by Kelvin probe force microscopy (KFM). It was found that the removal of the surface potential shielding effect of the adsorbed water-related layer by means of thermal treatment was effective in the observation of low potential regions at around the dislocations. The low potential regions at dislocations indicated that the dislocations of AlGaN/GaN heterostructure and n-GaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…By comparing the CPD map to the topography, we can see that dislocation pits are located in areas with higher CPD (between 150 and 200 mV difference), which, in our setup, means more positively charged regions. This finding differs from previous studies, which observed/predicted negatively charged dislocations. However, these negative fixed charges at dislocations are not seen in every sample: some studies measured no charge density on TDs, , and others reported even positively charged dislocations. KPFM is sensitive to the surface states and, therefore, to any possible contamination layer (oxide, carbon complexes, adsorbed water, etc. ), which, in turn, depends on the growth process, the cleaning process, if any, and the time and conditions of storage, making the comparison of samples difficult.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…By comparing the CPD map to the topography, we can see that dislocation pits are located in areas with higher CPD (between 150 and 200 mV difference), which, in our setup, means more positively charged regions. This finding differs from previous studies, which observed/predicted negatively charged dislocations. However, these negative fixed charges at dislocations are not seen in every sample: some studies measured no charge density on TDs, , and others reported even positively charged dislocations. KPFM is sensitive to the surface states and, therefore, to any possible contamination layer (oxide, carbon complexes, adsorbed water, etc. ), which, in turn, depends on the growth process, the cleaning process, if any, and the time and conditions of storage, making the comparison of samples difficult.…”
Section: Resultscontrasting
confidence: 63%
“…This finding differs from previous studies, which observed/predicted negatively charged dislocations. 23−29 However, these negative fixed charges at dislocations are not seen in every sample: some studies measured no charge density on TDs, 30,31 and others reported even positively charged dislocations. 32−34 KPFM is sensitive to the surface states and, therefore, to any possible contamination layer (oxide, carbon complexes, adsorbed water, etc.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are difficulties in extracting accurate surface potential values, particularly due to the humidity level in the atmosphere during the measurement [23]. Nevertheless, qualitative and quantitative trends for surface potential main values were inferred.…”
Section: B Surface Characterizationmentioning
confidence: 99%